2013
DOI: 10.1093/schbul/sbt195
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Admission With Infection During Childhood and Risk for Psychotic Illness--A Population-based Cohort Study

Abstract: A growing body of literature suggests that exposure to infections, particularly maternal infections, during pregnancy confers risk for later development of psychotic disorder. Though brain development proceeds throughout childhood and adolescence, the influence of infections during these ages on subsequent psychosis risk is insufficiently examined. The aim of this study was to investigate the potential association between infections during childhood and nonaffective psychoses in a large population-based birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 27 publications
12
45
0
Order By: Relevance
“…These findings are consistent with a growing body of evidence for increased risk of adult mental disorder among offspring of mothers exposed to infection during pregnancy (Brown, ; Hamdani et al., ; Jablensky et al., ; Selten & Morgan, ), as well as individuals exposed to infectious and autoimmune diseases throughout the life course (Abrahao et al., ; Benros et al., , ; Blomstrom et al., ; Dalman et al., ; Kohler et al., ; Koponen et al., ). Among all of the risk exposures examined here, the highest odds of developmental vulnerability were observed for offspring exposed to maternal mental illness first diagnosed prior to the child's birth, suggesting a possible role for inherited genetic susceptibility to mental disorder, rather than the effects of stress on the child that may be associated with being exposed to the behavior of a mentally ill mother during the early childhood years.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings are consistent with a growing body of evidence for increased risk of adult mental disorder among offspring of mothers exposed to infection during pregnancy (Brown, ; Hamdani et al., ; Jablensky et al., ; Selten & Morgan, ), as well as individuals exposed to infectious and autoimmune diseases throughout the life course (Abrahao et al., ; Benros et al., , ; Blomstrom et al., ; Dalman et al., ; Kohler et al., ; Koponen et al., ). Among all of the risk exposures examined here, the highest odds of developmental vulnerability were observed for offspring exposed to maternal mental illness first diagnosed prior to the child's birth, suggesting a possible role for inherited genetic susceptibility to mental disorder, rather than the effects of stress on the child that may be associated with being exposed to the behavior of a mentally ill mother during the early childhood years.…”
Section: Discussionsupporting
confidence: 83%
“…The primacy of infectious agents in conferring risk for later mental disorders should therefore not be assumed. Moreover, comparable increases in risk for schizophrenia and mood disorders are also associated with exposure to infection during childhood (Abrahao, Focaccia, & Gattaz, ; Benros et al., , ; Blomstrom et al., ; Dalman et al., ; Kohler et al., ; Koponen et al., ; Liang & Chikritzhs, ) and adolescence (Nielsen, Benros, & Mortensen, ; Nielsen, Laursen, & Mortensen, ; Sorensen et al., ), suggesting that events in developmental periods other than gestation also contribute to risk of mental disorders. Indeed, two recent studies have reported small but significant associations between early childhood vulnerability indicators and childhood infection (Kariuki et al., ), as well as with other chronic health conditions (Bell, Bayliss, Glauert, Harrison, & Ohan, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is based on current understanding that events that increase stress and or directly alter developmental processes lead to persistent psychotic states. The best evidence for this approach comes from epidemiological data showing small but statistically significant and reliable increases of psychotic illnesses among populations that experience early life and prenatal stressors ranging from infection, to famine, death of the father during pregnancy and war in general [98101]. There is even stronger evidence that exposure to marijuana prior to and during adolescence can alter the normal developmental trajectory and lead to a permanent state of psychosis, reminiscent of schizophrenia [102, 103].…”
Section: Manipulationsmentioning
confidence: 99%
“…A number of studies have found that a range of infections (203)(204)(205)(206) during childhood increase the risk of later schizophrenia and other psychotic disorders (203). Originally it was thought that associations were restricted to infections of the Central Nervous System (CNS) due to their direct neurological involvement (203,206).…”
Section: The Case For Mediation and Moderationmentioning
confidence: 99%
“…A number of studies have found that a range of infections (203)(204)(205)(206) during childhood increase the risk of later schizophrenia and other psychotic disorders (203). Originally it was thought that associations were restricted to infections of the Central Nervous System (CNS) due to their direct neurological involvement (203,206). However, it is now believed that a range of common infections not directly involved in the CNS (207), and even atopic disorders including asthma and eczema (208,209), may increase schizophrenia risk.…”
mentioning
confidence: 99%